Community-based breeding programs and animal health interventions in the extensive production system of Ethiopia: a political economy and stakeholder analysis - Tesfa, Assemu; Taye, Mengistie; Haile, Aynalem; Nigussie, Zerihun; Najir, Dina; Mekuriaw, Shigdaf; Demis, Chekole; Duressa, Asmamaw; Gehano, Gelano; Dussie, Tsegaye; Chalchisa, Tamiru; Sheferaw, Desie; et al. (Frontiers Media, 2025)
The aim of this study was to identify potential institutions, their contributions, and linkages among them for the successful implementation of Community-Based Breeding Programs (CBBP) and Animal Health Interventions (AHI) in Ethiopia. Stakeholder analysis was done using the Institutional Analysis and Development Framework, comprising three basic stages: context, application of stakeholder analysis methods, and action. Power and interest matrix analysis was used to segregate and prioritize the stakeholders based on their interest, influence, and power in running and influencing the selected interventions. Data were generated through focus group discussions, key informant interviews, and literature review. To rate the contribution level, map the relationship, and identify their influence, stakeholders were categorized based on their type of contribution. In both interventions, 43 stakeholders were identified, of which 13 participated in both interventions. Governmental and non-governmental organizations, the private sector, and projects were identified to have a stake in both interventions. For CBBP, 17 stakeholders with 30 linkages and for animal health interventions, 15 stakeholders, with 36 potential linkages were mapped. Based on the power-interest matrix analysis, stakeholders such as the Ministry of Agriculture, national and regional research institutes, and projects such as the International Center for Agricultural Research in the Dry Areas and Health of Ethiopian Animals for Rural Development (HEARD), have a high level of power and interest to implement both interventions. Absence of strong and continuous monitoring and evaluation, absence of sustainable financial support, and low level of interest in stakeholders supporting the interventions technically were identified as strategic gaps to be considered. Working on the political economy and stakeholder analysis is crucial to understand the formal and informal linkages, the power and influence of actors, and the outcome attained through the joint contributions of these stakeholders. Increased collaboration in interventions could generate synergistic effects, reduce conflicts of interest, and strengthen accountability between and among stakeholders. Privatizing animal health services through graduate veterinarians could enable access to wider areas of pastoralists and small ruminant producers. Stakeholders with high power and low interest need to be approached and periodically sensitized to use their power for the sustainability of the interventions.